UJI TOKSISITAS EKSTRAK DAUN WARU (Hibiscus tiliaceus L.) TERHADAP LARVA Artemia salina Leach SERTA IDENTIFIKASI GOLONGAN SENYAWANYA - Rustini, Ni Luh; Ariati, Komang; Indah Purna Dewi, A. A.; Dira Swantara, I Made (Jurnal Kimia (Journal of Chemistry), 2015)
The “Brine Shrimp Lethality Test” (BSLT) is a preliminary test used to monitor the bioactive compounds from natural products as anti-cancer. This research aimed to determine of toxic compounds in the leaf of waru (Hibiscus tiliaceus L.). Maceration of 900 g waru leaf powder with 7000 mL of ethanol (5x24 hours) yielded 53,19 g ethanol extract with toxicity tests to larvae of Artemia salina Leach (LC 50 ) of 79.43. The ethanol extract was partitioned to yield 1,81 g of n-hexane (LC 50 = 63,09 ppm), 1,52 g of chloroform (LC 50 = 1000 ppm) and 50,08 g of aqueous extract (LC 50 = 316 ppm). The most toxic, n-hexane extract, was then separated , purified and identified. n-hexane extract was separated by column chromatography with silica gel 60 as stationary phase and n-hexane-chloroform-ethanol (5:4:1) as mobile phase to yield 7 fractions. Fraction one (F1) with a single stain on thin-layer chromatography was the most toxic (LC 50 = 398 ppm). Identification with phytochemical test, UV-Vis spectrophotometer and IR spectrophotometer,  showed that the isolate contained sterol compounds.
Keywords: leaf of waru , Hibiscus tiliaceus L., toxicity, Artemia salina Leach